ASMT gene polymorphisms are associated with Autism Spectrum Disorder (ASD) symptom severity in a South African population - De Waal, Margaretha (Department of Molecular and Cell Biology, 2017)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterised by behavioural and social impairments. ASD shows evidence of a genetic aetiology, with a large body of research linking ASD to polymorphisms in several different genes and gene families, including those involved in circadian rhythm generation and melatonin biosynthesis. Sleep disorders are highly comorbid with ASD in both children and adults, and range from sleep onset delay, phase shift and sleep disruption. These parasomnias can have a significant impact on the quality of life for persons with ASD and their families, and sleep deprivation can feed into the behavioural deficits in ASD. Melatonin supplementation is often prescribed to assist in alleviating the above mentioned sleep dysfunction. Melatonin is a hormone in the circadian clock system, and is a biochemical signal for darkness to synchronise peripheral cells to the master oscillator. Clinical trials reported that melatonin supplementation at night assists in sleep initiation. However both the mode of action of supplemental melatonin, as well as whether melatonin deficiency is common in ASD, remains unclear. Furthermore, any research on ASD is often hamstrung by the heterogeneous nature of the disorder, necessitating clear phenotyping. This study examines single nucleotide polymorphisms (SNPs) in the gene acetylserotonin methyl transferase (ASMT), which encodes an enzyme in melatonin biosynthesis, in a South African ASD cohort (n=28) and controls (n=6). All participants completed and Autism Diagnostic Observation Schedule-2 assessment that allowed partitioning of the ASD individuals into ASD endophenotypes, to reduce phenotyping heterogeneity. This study found SNPs previously associated with ASD in the promoter and intronic region. Additionally, this study found novel SNPs, and a SNP in a putative transcription factor binding site not previously associated with ASD. The associations found between SNPs and ASD endophenotypes, together with the positions of the SNPs, suggest a potential link between ASMT polymorphisms and ASD symptom severity. Further research, using language assessment tools as well as quantitative measures of melatonin and sleep disruption, may establish the role of melatonin in language impairment in ASD.